The spirits of the law. On the instituting tensions of Legislative Decree 62/2024 regarding the personalised project for people with disabilities: A study of legal animism (Sociologia del diritto, 2025)
Since a 2021 law, the Italian welfare system has been undergoing extensive regulatory reform aimed at enabling persons with disabilities to fully exercise their civil and social rights, in accordance with the Constitution and in compliance with the United Nations Convention on the Rights of Persons with Disabilities. This article focuses on the part of the reform contained in Legislative Decree 62/2024, which identifies the personalised and participatory project as the most effective modus operandi for social and health services to promote autonomy and foster de-institutionalisation. The article reconstructs the historical factors that have given centrality to tailored planning, starting from the decisive role of the effects of COVID-19 on persons with disabilities. The interpretative hypothesis is that the decree bears the marks of a constitutive dualism due to the coexistence of contrasting instances on the self-determination of persons with disabilities.
Keywords: disabled people; personalised project; spirit of the laws; welfare reform in italy; legislative decree 62/2024